"Agile" and "uptight" genres: the corpus-based approach to language change in progress - Hundt, Marianne; Mair, Christian (International journal of corpus linguistics, 1999)
This paper is a follow-up study to previous investigations based on the analysis of parallel British and American corpora from the early 1960s and 1990s. It focuses on variables that are suspected to contribute to the growing "colloquicdisation " of the norms of written English, that is, a narrowing of the gap between spoken and written norms. Such a shift in stylistic preferences has been observed in both socio-cultural approaches to language and corpus-based studies. Contrasting material from the press and academic prose sections of standard one-million-word corpora, we are able to show that the two genres differ in the degree to which they are open to innovations or prone to retain conservative features. What we are proposing is a cline of openness to innovation ranging from "agile " to "uptight" genres.
Gesehen am 02.02.2021